Caffeic Acid Has Antiviral Activity against Ilhéus Virus In Vitro - Saivish, Marielena Vogel; Pacca, Carolina Colombelli [UNESP]; da Costa, Vivaldo Gomes [UNESP]; de Lima Menezes, Gabriela; da Silva, Roosevelt Alves; Nebo, Liliane; da Silva, Gislaine Celestino Dutra; de Aguiar Milhim, Bruno Henrique Gonçalves; da Silva Teixeira, Igor; Henrique, Tiago; Mistrão, Natalia Franco Bueno; Hernandes, Victor Miranda; et al. (MDPI, 2023)
Ilhéus virus (ILHV) is a neglected mosquito-borne flavivirus. ILHV infection may lead to Ilhéus fever, an emerging febrile disease like dengue fever with the potential to evolve into a severe neurological disease characterized by meningoencephalitis; no specific treatments are available for this disease. This study assessed the antiviral properties of caffeic acid, an abundant component of plant-based food products that is also compatible with the socioeconomic limitations associated with this neglected infectious disease. The in vitro activity of caffeic acid on ILHV replication was investigated in Vero and A549 cell lines using plaque assays, quantitative RT-PCR, and immunofluorescence assays. We observed that 500 µM caffeic acid was virucidal against ILHV. Molecular docking indicated that caffeic acid might interact with an allosteric binding site on the envelope protein.
Keywords: antiviral activity; caffeic acid; Ilhéus virus; in silico analysis; inhibition